Effect of climatic parameters on yield and yield components in Hevea - Dey S K; Devakumar A S; Nair D B; Rajagopal R; Sathik M; Sethuraj M R; Vijayakumar K R (National Symposium on the Role of Plant Biotechnology in Improving Agriculture-Challenges and Opportunities and Physiological and Biochemical basis of crop yield, 23-25 March, 1995, 1995)
Seasonal variation of yield in Hevea is a well known fact which affects the optimum annual productivity of crop. Attempts were made to study the effect of climatic parameters on yield and yield componenets. Initial flow rate (F) is positively and plugging index (P) negatively correlated with yield. Path coefficient analysis reveals that high temperature reduces the soil moisture (SM) and SM in turn influences the plugging index, ultimately resulting in reduction of yield. In addition to that high temperature had direct effect on dry rubber content (Cr), which also is an yield component. Effect of Cr on yield was not prominent, hence yield had not been much affected. Effect of various climatic parameters on different clones were also discussed. High temperature <<Low soil moisture<<High Plugging<<Low yield.
Keywords: Climatic parameters; Hevea; Yield